Proceedings of the 2004 Workshop on Location-Aware Computing: Applications - LaMarca, Anthony; Scott, James; Smith, Ian (2004 Workshop on Location-Aware Computing (Part of UbiComp 2004), 2004)
In the near future, most tourists will carry mobile devices of some sort enabling them to access and browse wirelessly distributed “information clouds” (WiFi in particular). Such information clouds can be used to enhance how tourists explore and experience cities (e.g., Cheverst et al. 2000). We are particularly interested in dynamic aspects of tourism settings and how visitors can be made aware of them. The city of Darwin (like many other cities) features a number of interesting aspects that may be difficult to recognize and explore for someone not familiar with the city. Examples include nice restaurants hidden in boring looking alleys and cosy pubs not colocated with other popular venues. It is important to note that value and even existence of these “attractions” may change over time whereas more traditional attractions (e.g., castles, churches, museums) considered in related research are unlikely to change. Furthermore, there are a number of aspects or events that are dynamically changing in time and place (e.g., pub “happy hours”, lunch specials, evening live performances, Sunday afternoon Jazz). Such events are notoriously difficult to track for tourists. Supporting tourists in exploring these dynamic aspects of the city requires: 1. informing tourists about businesses of interest as well as dynamically changing attractions (“events”), and possibly 2. guiding them to the location of the business or attraction. We are interested in ways for businesses and event organizers to push relevant information and way descriptions into information clouds accessed by tourists. Work most relevant to this workshop is the use of location-aware egocentric navigation for “smart guiding”.